Effects of Perceived Ease of Use, Security, Perceived Usefulness, and Trust on the Use of E-Wallet "DANA" on ZXY Polytechnic Students - Ningsih, Afrina Nurulda; Andayani, Nur Rahmah (Journal of Applied Business Administration, 2024)
Nowadays, technological developments have an impact on business transactions, including payment systems. One of the tangible proofs of the technological development of this digital payment system is a digital wallet or e-wallet. This study aims to determine, test, and identify the extent to which the variables perceived ease of use, security, perceived usefulness, and trust have an influence on ZXY Polytechnic students in using the DANA e-wallet. This study uses a quantitative approach with the number of samples taken as many as 96 respondents and the population comes from ZXY Polytechnic students who are determined by nonprobability sampling techniques using the quota sampling method. The data collection technique is by literature study and distributing questionnaires. Data processing techniques using SPSS version 29.0. The results of this study indicate that the variables perceived ease of use and security do not have a significant effect on interest in use. While the variables of perceived usefulness and trust have a significant effect on interest in use.